2002
DOI: 10.1002/ajh.10020
|View full text |Cite
|
Sign up to set email alerts
|

Soluble angiogenic factors: Implications for chronic myeloproliferative disorders

Abstract: The role of angiogenesis for the progressive growth and metastatic process of tumours is well established. What is not clear, though, is the clinical prognostic signi®cance of the angiogenic factors in malignant haematological diseases. In this study, we have assessed the plasma and serum levels of two major angiogenic factors, vascular endothelial growth factor (VEGF) and basic ®broblast growth factor (b-FGF) in 55 patients affected by chronic myeloproliferative disorders (CMD). This series included 25 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 27 publications
7
40
0
13
Order By: Relevance
“…Yet, symptoms of chronic inflammation are observed both in JAK2V617F-mutated MPN and in MPN with no mutation of JAK2, particularly primary myelofibrosis (Geissler et al, 1998;Le Bousse-Kerdile´s and Martyre´, 1999;Wickenhauser et al, 1999;Hermouet et al, 2002;Musolino et al, 2002;Corre-Buscail et al, 2005;Panteli et al, 2005). The findings of the present study of PV patients support the opposite reasoning, that is, that upregulation of certain cytokines linked to inflammation is independent of the acquisition of the JAK2V617F mutation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Yet, symptoms of chronic inflammation are observed both in JAK2V617F-mutated MPN and in MPN with no mutation of JAK2, particularly primary myelofibrosis (Geissler et al, 1998;Le Bousse-Kerdile´s and Martyre´, 1999;Wickenhauser et al, 1999;Hermouet et al, 2002;Musolino et al, 2002;Corre-Buscail et al, 2005;Panteli et al, 2005). The findings of the present study of PV patients support the opposite reasoning, that is, that upregulation of certain cytokines linked to inflammation is independent of the acquisition of the JAK2V617F mutation.…”
Section: Discussionsupporting
confidence: 74%
“…The '46/1' haplotype is also associated with chronic inflammation, notably inflammatory bowel disease (Ferguson et al, 2010). Interestingly, although most evident in primary myelofibrosis, signs of chronic inflammation, such as increased production of inflammatory cytokines, interleukin (IL)-6 and vascular endothelial growth factor, are also observed in PV and in ET (Wickenhauser et al, 1999;Musolino et al, 2002;Panteli et al, 2005;Le Bousse-Kerdile´s and Martyre´, 1999). Inflammation-associated symptoms were long considered consequences of activating mutations of JAK2, but recent clinical trials of JAK2 antagonists showed that drugs not strictly specific for JAK2 were most efficient in reducing inflammation-linked cytokine levels and symptoms, indicating that molecules other than JAK2 were likely involved (Tefferi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…27 VEGF is a critical angiogenic factor that is crucial to disease progression and metastases in solid tumors, 28 and it has been suggested to act as a mediator of disease-associated angiogenesis in patients with myeloid leukemia. 29,30 However, only a few reported studies have shown that VEGF has a prognostic role in predicting patient outcome in leukemia 31 In this study, we have shown that VEGF is highly expressed in 52% of AML patients. VEGF expression is associated with several clinical features.…”
Section: Discussionmentioning
confidence: 66%
“…Angiogenesis expressed as angiogenic factor’s serum or plasma levels, has been also evaluated in patients with ET [25,26,27,28]. Molica et al [25] found increased serum levels (adjusted for platelet count) in ET patients, but lower than in patients with CML and MMM.…”
Section: Discussionmentioning
confidence: 99%